Creation and utilization of the my balas bag online system (MBB) (Southeast Asian Journal of Technology and Science, 2023)
The My Balas Bag Online System (MBB) is an online platform for recording the accumulation of reward points received by customers who buy in small shops without using plastic bags. The problem statement is that customers are less aware of the dangers of using disposable plastic bags. The second problem is because there is no encouragement from retailer grocery to customers not to use plastic bags and retailer grocery do not have an affordable platform or tools as an initiative to record the accumulation of reward points given to customers who buy without plastic bags. The objectives of this project are to design, develop and implement an online system in real situation. Methodology used is Prototype, whereby the developing of system is simultaneously administered with the implementation. In conclusion, this project helps to reduce using of plastic bag while buying goods